Impeachment as Perverse Circuit in Politics - Pessoa do Amaral, Muriel Emídio (2021)
This article's intention is to recognize perverse and antipolitician signs over Dilma Roussef's impeachment process, that happened in 2016.  Started from Hannah Arendt's conceptions about politics, this text recognizes the consumption and the acceptance of the magazines covers from Veja Magazine, one of the most read in Brazil, by anonymous people on their perverse standards. For that, the research uses as methodology the concept of culture circuit developed by Richard Johnson, in order to keep up with that perverse values were recognized and assumed since the magazine's production until the communication process of its circulation. Thereby, the research's results indicate that Dilma Roussef's impeachment process was produced from the destruction, at that time, of the stablished political space, in name of private passions which were spread as cultural and moral values.